Bone scintigraphy imaging of cardiac amyloidosis - Kuria, Issa Menge; Gitau, Samuel Nguku; Makhdomi, Khalid Bashir (World Journal of Nuclear Medicine, 2019)
Transthyretin-related cardiac amyloidosis (ATTR) amyloidosis is an aggressive, rapidly progressive, and fatal disease, for which several promising therapies are in development. This condition is frequently underdiagnosed because of the limited specificity of echocardiography and the traditional requirement for histological diagnosis. It is well known that 99mtechnetium-labeled bone scan radiotracers can localize in the myocardial amyloid deposits, but the use of this imaging modality to differentiate between the two subtypes has only lately been revisited. We report a case of a 76-year-old man with a clinical diagnosis of amyloidosis who underwent a bone scan that had features of ATTR amyloidosis. To the best of our knowledge, this is the first case report in Sub-Saharan Africa.
Keywords: AL; bone scintigraphy; cardiac amyloidosis; transthyretin ATTR